Analysis of Breastmilk-Based Nutrition on Reducing Morbidity in Premature Infants - Pratiwi, Dessy; Anggreani, Riska; Basrowi, Ray Wagiu (Journal of Indonesian Specialized Nutrition, 2024)
Preterm and low birth weight (LBW) births remain a health challenge in Indonesia, with the prevalence of preterm births reaching 7-16% and LBW babies at 11.5%. Preterm infants are prone to various health complications, such as respiratory distress and infections, which increase morbidity rates. Breastfeeding is an important strategy in the care of preterm infants because it contains components that strengthen the immune system, prevent health complications, and support optimal growth and development. This study aims to provide more specific scientific evidence on the effectiveness of breastfeeding in reducing the risk of health complications in preterm infants. The results showed that breastfeeding plays a crucial role in reducing morbidity rates in premature infants, as it contains nutrients, antibodies and growth factors that strengthen the infant's immune system. Exclusive breastfeeding helps reduce the risk of complications such as gastrointestinal infections and respiratory distress, which premature infants often experience. In addition, breastmilk supports brain and nervous system development, increasing preterm infants' chances of healthy growth and development, making it an important intervention in efforts to reduce morbidity rates in preterm infants.